Desenvolvimento de um sistema para caracterização de sensores de gases - Ponzoni, Andre Luiz de Lima (2007)
A system for samples characterization by thermoelectroresistometry (TER) was developed, including the code for the acquisition data program for such system. TER consists on the measure of the electric resistance in function of the temperature. The system was tested for samples of oxides mixtures achieved after a thermal treatment of the freeze-dried powders. Mixtures of powders of hematite (Fe2O3) and manganese acetate tetra-hydrated [(CH3COO)2Mn·4H2O], with a molar ratio for cations of Fe:Mn=2:1, were obtained by freeze-drying. The freeze-dried powders were thermal treated at 400 ºC/2h, the X-ray diffraction (XRD) spectra indicate the presence of hematite and hausmanite (Mn3O4). For the samples treated at 700 and 1000 ºC, XRD indicated the presence of manganese oxide (Mn2O3) and hematite, and iron manganese oxide (FeMnO3) and hematite phases, respectively. TER showed that the sample treated at 400 ºC is sensitive to methane gas (CH4). Nevertheless, the sensitivity only occurs in the specific condition of low atmospheric pressure and in the exclusively presence of the gas.